The Use of Prepositions among EFL Learners: A Systematic Review - Damayanti Damayanti; Hanna Sundari (Scope : Journal of English Language Teaching, 2022)
As a second/foreign language learner, one should understand the rules and convention of the language s/he learns and how to use it. Therefore, s/he needs to master the language to be able to have good communication with others. One aspect that needs to be learned is parts of speech such as nouns, pronouns, verbs, adjectives, adverbs, conjunctions, and prepositions. Prepositions play a significant role in helping students increase their language skills. However, many students still face difficulties in learning its type of parts of speech. The purpose of this study is to examine the trends and main findings of the studies about the main error types and causes in using prepositions among second/foreign language learner. For this objective, articles from databases comprising Google Scholar, Eric, and Garuda Ristek were reviewed, and overall, selected articles were analysed. As the research methodology, systematic review was performed. A content analysis was used to evaluate the articles. According to the results of the study, the main error type in using prepositions among the learners is the wrong use of prepositions. In the meantime, the main cause of the errors made by the learners in using prepositions is the interlingual interference